The Interplay Between Economic Freedom and Tax Revenue Performance: Panel Evidence from SADC - Baneng Naape (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study aims to scrutinize the interplay between economic freedom and tax revenue performance in 14 SADC countries. The study makes use of dynamic panel data spanning from 2000 – 2017 with 238 year-country observations. The econometric modeling applied includes Generalized Methods of Moments and Cross-country Correlations. The dynamic panel estimation results indicate that both conventional and unconventional determinants of tax revenue mobilization are statistically significant in explaining variations in tax revenue performance. In contrast to earlier studies, the researcher found that economic freedom exhibits a negative impact on tax revenue mobilization. These findings can be based on the assumption that African countries are characterized by agrarian activities which take place in the informal sector and are thus are difficult to regulate and tax. As a result, the benefits of economic freedom cannot be fully realized. The policy implication is for African countries to invest substantially in the manufacturing sector to increase tax revenue and eliminate the substantial informal sector. Further to this, governments in SADC countries should focus more on reducing red tape and unnecessary bureaucracy to enhance the ease of doing business and realize the full benefits of economic freedom.